2023
DOI: 10.1111/hdi.13071
|View full text |Cite
|
Sign up to set email alerts
|

Chronic kidney disease‐associated pruritus in patients undergoing hemodialysis: Xerosis and topical therapy

Abstract: Chronic kidney disease‐associated pruritus (CKD‐aP) is a common and distressing symptom for patients with CKD and a difficult challenge for nephrologists and dermatologists. Recent results showed the multifactorial nature of the pathophysiology, and therapeutic trials were only successful in certain subsets of patients. The clinical manifestations are varied, with xerosis being the most common dermatological manifestation and correlated with the intensity of CKD‐aP. A better understanding of the pathophysiolog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 86 publications
0
1
0
Order By: Relevance
“…Uremic toxins, skin barrier impairments, neurogenic pathways, immune dysregulation, and other factors are thought to contribute to UP( Narita et al, 2008 ; Ko et al, 2023 ). Studies have indicated that low skin moisture in dialysis patients may be one of the contributing factors to induce pruritus ( Morton et al, 1996 ; Ko et al, 2023 ; Krismi et al, 2023 ). Moreover, the significant increase in the number of dermal mast cells in UP patients is also considered as an important factor promoting skin itching ( Robertson et al, 2016 ; Simonsen et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…Uremic toxins, skin barrier impairments, neurogenic pathways, immune dysregulation, and other factors are thought to contribute to UP( Narita et al, 2008 ; Ko et al, 2023 ). Studies have indicated that low skin moisture in dialysis patients may be one of the contributing factors to induce pruritus ( Morton et al, 1996 ; Ko et al, 2023 ; Krismi et al, 2023 ). Moreover, the significant increase in the number of dermal mast cells in UP patients is also considered as an important factor promoting skin itching ( Robertson et al, 2016 ; Simonsen et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%